Cultural ecologies, human sensations and natural environments: A transitivity analysis of I am Afraid of Muslims - Fauzia Janjua (Cogent Arts & Humanities, 2022)
Ecocritical scholarship has encouraged diverse contributions from varied disciplines to the discussion of environmental issues across the globe. Given the magnitude of the problem and the frequency of the mutilation it carries along, there is a call for every segment of the society to contribute towards the theme. Literature being one of the strongest social stimulants has taken up the responsibility to address the issue from multivariate perspectives. Ecopoetry, one of the recently evolved literary genres, construes environmental representation as a pertinent category of literary, artistic, and political deliberation, often in conjunction with a focus on developing sensation, generating awareness, raising consciousness and problem-solving. Waqas Khwaja, one of the Pakistani English poets, writing “I am afraid of Muslims” Waqas Khwaja, articulates human-nature relation situating the responsibility of the devastation of nature on every born human soul beyond the boundaries of ethnicity, religion, knowledge and ideology. The present study offers an ecocritical analysis of the poem appraising the ideological stance built up by the poet by exploring the relationships construed through the consumption of the linguistic creativity and symbolic mapping of the concepts. The study revealed that Pastoral, as one of the forms of environmental imagination, synonymous with the idea of (re)turn to a less urbanized, more ‘natural’ state of existence formed the core thesis to express the environmental values and to render voice to nature. The study also traces global political ideologies entrenched in the modern world of human beings.